512Challenges and opportunities to appropriate antibiotic prescribing: a survey of clinicians' perceptions in Australia. (2nd September 2021) - Laka, Mah; Milazzo, Adriana; Merlin, Tracy
Abstract: Background: Emerging antibiotic resistance is significant threat to global public health. There is evidence on sub-optimal prescribing as a contributing factor to antibiotic resistance. This study aimed to identify behavioral determinants of antibiotic prescribing that may help design effective interventions. Methods: A cross-sectional survey was undertaken with clinicians (hospital and primary care) in Australia from June–October 2019. Multivariate logistic regression was used to determine if clinicians' characteristics, and guidelines' use, are associated with barriers of appropriate antibiotic prescribing. Results: Inappropriate prescribing behavior is not limited to clinicians' practices, but also relate to patients' expectation and clinical culture. Lack of data for evidence-based decision-making and diagnostic uncertainty contribute to sub-optimal antibiotic prescribing. Different care settings and clinicians' experience influence perceptions of whether unavailability of information, delay in diagnostic results and patient expectations regarding treatment led to inappropriate prescribing behavior. Respondents in primary care and with less experience were more likely to consider that patient demands (primary care: OR 1.76, 95%CI 1.34–2.68 & experience (1-10 years): OR 1.34, 95%CI 1.07–1.59) and lack of data required for decision-making (primary care: OR 1.59, 95%CI 1.09–2.10 & experience (1-10 years): OR 1.63, 95%CI 1.13–1.87) are barriers to appropriate prescribing. Conclusions: A complex network of social, contextual and clinical factors influence prescribing practices. A holistic approach addressing clinicians' practices, setting requirements and patient expectations must be considered. Key messages: For optimal antibiotic prescribing, there is a need to focus on contextual requirements, shared decision-making and availability of relevant information at point-of-care.